Dynamic deployment algorithm for multi-controllers based on bidirectional matching in software defined networking - Tao HU; Jianhui ZHANG; Weigong KONG; Sen YANG; Lujia CAO (Tongxin xuebao)
Aiming at the controller load imbalance problem in distributed SDN,a multi-controller dynamic deployment algorithm based on bidirectional matching was proposed.Through collecting hop counts,delay and flow information in the network periodically,match lists of switch and controller was built respectively.According to the principle of optimal queuing,switches and controllers were selected from two match lists for implementing bidirectional matching,and the relationship of matching with the help of simulated annealing algorithm was optimized,which achieved dynamic deployment for multi-controller in distributed network.Results show that,compared with the existing approaches,this algorithm can match the connections between switches and controllers reasonably,and reduce the queue delay of flow request effectively.Moreover,and the controller load balancing rate has increased by 17.9% at least.